Aneurysms in pediatric age: a challenging and rare disease entity. Issue 3 (July 2015) - Sayed, Ahmed; Elsadat, Ahmed; Mashaal, Marwa
Abstract : Introduction: Pediatric arterial aneurysms are extremely rare. Their etiology can be congenital, mycotic, following infective endocarditis, post-traumatic pseudoaneurysms, or vasculitis. The treatment strategy in children is not very clear because of the small number of cases. Methods: This study included eight children with arterial aneurysms, which included one thoracic, two abdominal aortic, one iliac, three upper-extremity, and two carotid aneurysms. Revascularization was performed using an autogenous vein whenever feasible. Anastomoses were performed with interrupted sutures with nonabsorbable material to allow for future growth of the vessels. Ligation was allowed only after ensuring that the distal collateral circulation was adequate. Results: Eight aneurysms were reconstructed and one carotid aneurysm was ligated. No neurologic events occurred after the carotid ligation. Follow-up ranged between 4 months and 4 years and showed no recurrences or occlusion of reconstructed aneurysms, as detected clinically and radiologically. The grafts used for reconstruction – including the synthetic ones – were found to be growing with the age of the children. In one aortic case, there was mild stenosis in one of the iliac limbs, but that was asymptomatic. The extremity aneurysms repair were uneventful, with good flow in the affected extremity. Conclusion: Repair of aneurysms in children is feasible and yields good midterm results. Management is usually individual and tailored to each case. Finding the suitable conduit is a challenge, and autogenous veins are preferred whenever available.